Data Analysis of Oil Palm (Elaeis Guineensis) Root Carrying Capacity in Mitigating Landslide Risk Due to Extreme Rainfall: A Comparative Literature Study - Muhammad Nabil Rizki Al Fatih (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study examines the carrying capacity of oil palm (Elaeis guineensis) roots in mitigating landslide risk under extreme rainfall conditions in Indonesia. The research was motivated by increasing deforestation and the conversion of natural forests into oil palm monoculture plantations, which reduce slope stability and increase disaster vulnerability. The objective of this study was to analyze the effectiveness of oil palm root systems in maintaining soil stability using the Index of Root Anchoring (IRA) and Index of Root Binding (IRB) parameters. This research employed a qualitative descriptive method with a comparative literature study approach. The population consisted of scientific literature discussing root biomechanics, soil stability, and landslide mitigation, while the sample included selected journals, reports, and scientific references relevant to oil palm root characteristics. Data were collected through literature documentation techniques and analyzed descriptively by comparing IRA and IRB values from previous studies. The results showed that oil palm roots possess relatively strong horizontal binding capacity with an IRB value of approximately 0.0256, but very weak vertical anchoring capacity with an IRA value of approximately 0.004. The conclusion indicates that oil palm plantations can reduce surface erosion but are unable to provide adequate deep-soil reinforcement under extreme rainfall conditions, thereby increasing landslide susceptibility